2009
DOI: 10.1007/s00415-009-5057-y
|View full text |Cite
|
Sign up to set email alerts
|

1H MR spectroscopy of gray and white matter in carbon monoxide poisoning

Abstract: Carbon monoxide (CO) intoxication leads to acute and chronic neurological deficits, but little is known about the specific noxious mechanisms. (1)H magnetic resonance spectroscopy (MRS) may allow insight into the pathophysiology of CO poisoning by monitoring neurochemical disturbances, yet only limited information is available to date on the use of this protocol in determining the neurological effects of CO poisoning. To further examine the short-term and long-term effects of CO on the central nervous system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…To the best of our knowledge, only one case report showed recovery the level of DAT availability in CO-poisoning patients at a 14-month follow-up (Kondziella et al, 2009). DAT receptors are located on the dendrites of the nerve cells projecting to the striatum from the substantia nigra.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To the best of our knowledge, only one case report showed recovery the level of DAT availability in CO-poisoning patients at a 14-month follow-up (Kondziella et al, 2009). DAT receptors are located on the dendrites of the nerve cells projecting to the striatum from the substantia nigra.…”
Section: Discussionmentioning
confidence: 92%
“…The clinical symptoms of CO poisoning are non-specific and varied, including cognitive dysfunctions, personality changes, urine and fecal incontinence, gait disturbances, parkinsonism and other movement problems, depression, anxiety and mutism (Ernst and Zibrak, 1998;Hurley et al, 2001;Kesler et al, 2001;Hay et al, 2002;Parkinson et al, 2002;Porter et al, 2002;Weaver et al, 2002;Pulsipher et al, 2006;Kondziella et al, 2009;Weaver, 2009;Chang et al, 2010;Ku et al, 2010;Yang et al, 2011). The cognitive impairment caused by CO poisoning involves multiple domains, such as attention, visual and verbal memory, executive function, calculation, and visuospatial function (Hurley et al, 2001;Kesler et al, 2001;Hay et al, 2002;Parkinson et al, 2002;Porter et al, 2002;Weaver et al, 2002;Pulsipher et al, 2006;Kondziella et al, 2009;Chang et al, 2010Chang et al, , 2011. Cognitive impairment is one of the most serious sequelae of CO poisoning because it may prevent the full recovery of pre-morbid functions in CO poisoning patients (Hurley et al, 2001;Weaver et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When attention is focused on the period in which each metabolite appears, these studies reported that the Cho/Cr ratio increased earliest in metabolites and decreased in the late period of the chronic phase, the NAA/Cr ratio began to decrease at the earliest from 3 to 4 weeks, and lactate began to appear at the earliest from 1 to 2 months after CO poisoning in patients with chronic symptoms. 56,[61][62][63][64][65][66][67] It is noteworthy that declines in NAA levels have been proposed as a good prognostic factor, as the NAA/Cr ratio correlates with symptom development, and the presence of lactate acts as a marker of irreversible brain damage because it has been observed in patients with severe chronic symptoms such as akinetic mutism and apallic state. MR spectroscopy findings by 3T MR imaging in the subacute phase in 29 patients with CO poisoning found that the Cho/Cr ratio in the centrum semiovale was slightly but significantly higher in patients with subsequent chronic-phase symptoms than in patients with transient symptoms in the acute phase.…”
Section: Mr Spectroscopymentioning
confidence: 99%
“…Some authors have mentioned the occurrence of inflammation in association with demyelination of the CNS in the acute phase among CO poisoned patients 8 9. Furthermore, previous studies in the chronic phase have reported increased Cho/Cr ratio in patients both with and without chronic neuropsychiatric symptoms 11 21 22 24. The present study showed that the mean Cho/Cr ratio in patients with chronic symptoms (both Groups P and D) was significantly higher than in patients with acute symptoms only (Group A) (figure 4).…”
Section: Discussionmentioning
confidence: 99%